Avaliação da cicatrização de feridas cutâneas em animais isentos de microbiota comensal - Maria Cecilia Campos Canesso (2014)
The commensal microbiota has a high impact on health and disease by modulating the development and homeostasis of host immune system. Immune cells are involved in virtually every aspect of the wound repair process; however, the impact of commensal microbiota on skin wound healing is largely unknown. Here, we evaluated the influence of commensal microbiota on tissue repair of excisional skin wounds by using germ-free (GF) Swiss/NIH mice. We observed that macroscopic wound closure rate is accelerated in the absence of commensal microbiota. Accordantly, histologically assessed wound epithelization was accelerated in GF in comparison with conventional (CV) Swiss/NIH mice. The wounds of GF mice presented a significant decrease in neutrophil accumulation and an increase in mast cell and macrophage infiltration into wounds. Interestingly, alternatively activated healing macrophage-related genes were highly expressed in wound tissue of GF mice. Moreover, levels of the anti-inflammatory cytokine IL-10, the angiogenic growth factor VEGF and angiogenesis were higher in the wound tissue of those mice. Conversely, scarring and levels of the pro-fibrogenic factor TGF-b1 were greatly reduced in GF mice wounded skin when compared to CV mice. Of note, conventionalization of GF mice with CV microbiota restored wound closure rate, neutrophil and macrophage accumulation, cytokine production and scarring to the same extent as CV mice. Overall, our findings suggest that, in the absence of any contact with microbiota, skin wound healing is accelerated and scarless, partially due to reduced accumulation of neutrophils, increased accumulation of alternatively activated healing macrophages and better angiogenesis at wound sites. Understanding how commensals regulate the healing process provides not only new directions in the pathophysiology of wounds, but also could support strategies to treat wounds by manipulating microbiota.